ECOLOGICAL ASSESSMENT OF SETU RIVER POLLUTION USING SAPROBIC INDEX AND AQUATIC BIOTA DIVERSITY - Kamtiyah Ningsih; Fuad Muhammad; Aris Mukimin (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- Combined saprobic index and plankton diversity assess Setu River pollution- Untreated batik wastewater affects river water quality and biodiversity- Eutrophic tolerant diatoms dominate polluted river sections- Benthic communities reflect persistent ecological disturbanceABSTRACTThe batik industry in Indonesia, especially in Pekalongan, has seen rapid growth since being recognized by UNESCO. However, this growth has brought increasing environmental concerns, particularly related to wastewater discharge from small-and medium-scale enterprises. This study assessed the ecological condition of the Setu River in South Pekalongan by integrating plankton diversity metrics and the saprobic index (SI) to evaluate the impact of batik effluents. Sampling was carried out in November 2024 at three representative locations selected to reflect different pollution gradients along the Setu River: upstream, the Jenggot Waste Water Treament Plant (WWTP) outfall, and downstream. Water quality showed a declining trend along the river, reflecting increasing anthropogenic pressures. Phytoplankton abundance ranged from 561 to 1,190 individuals/L, with dominant genera such as Navicula, Synedra, and Nitzschia, which are known indicators of organic pollution. Zooplankton was only observed at the downstream station, with a low diversity index (H’ = 0.6931), suggesting that water conditions were unfavorable for sensitive species. The saprobic index increased from 0.31 upstream to 0.93 downstream, indicating a light level of organic pollution. These findings indicate that the Jenggot communal WWTP may not be operating optimally, as reflected by the high concentrations of pollutant indicators near the outfall. Inadequate wastewater treatment exerts ongoing pressure on aquatic life, reducing biodiversity and disturbing ecological stability. This study emphasizes the urgency of improving wastewater management, particularly through the development of appropriate and low-cost technologies to support small-scale batik industries. Furthermore, plankton-based bioindicators offer a reliable, cost-effective method for monitoring ecological impacts in urban rivers subjected to industrial discharges.